Pyroptosis and Inflammasome-Related Genes-NLRP3, NLRC4 and NLRP7 Polymorphisms Were Associated with Risk of Lung Cancer - Jing X; Yun Y; Ji X; Yang E; Li P (Dove Medical Press, 2023)
Xin Jing,* Yuhui Yun,* Xiang Ji, Ende Yang, Pei Li Department of Thoracic Surgery, Tangdu Hospital, The Fourth Military Medical University, Xi'an, Shaanxi, 710038, People's Republic of China*These authors contributed equally to this workCorrespondence: Pei Li; Ende Yang, Department of Thoracic Surgery, Tangdu Hospital, The Fourth Military Medical University, Xi'an, Shaanxi, 710038, People's Republic of China, Email yanglinglipei@163.com; endeyangfmmu@163.comBackground: Cancer development and tumor immune microenvironment remodeling are closely linked to pyroptosis and inflammasome activation. However, little information is available in single nucleotide polymorphisms (SNPs) in pyroptosis and inflammasome-related genes in patients with lung cancer. This study aims to evaluate the associations between pyroptosis-related gene (NLRP3, NLRC4, and NLRP7) polymorphisms and the risk of lung cancer.Methods: The MassARRAY platform was used to genotype six SNPs of the NLRP3, NLRC4, and NLRP7 genes in 660 lung cancer cases and 660 controls.Results: Individuals with rs35829419-A, rs385076-C, and rs775882-T alleles exhibited a higher risk of lung cancer (p < 0.01), while rs212704-T appears protective (p = 0.006). The rs35829419-AA, rs385076-TC/CC, and rs775882-CT/TT genotypes were associated with various degrees of elevated risk of lung cancer (p< 0.02), whereas rs212704-TT was associated with a reduced risk of the disease (p=0.014). Genetic models analysis showed that rs35829419, rs385076, and rs775882 was associated with an increased risk of lung cancer, while rs212704 was related to a reduced risk in all three models (p < 0.05). The four SNPs remained significant in smoker and nonsmoker subgroups (p < 0.05). However, rs35829419 was correlated with risk of adenocarcinoma and small cell lung cancer, and rs212704 was only protective for squamous cell carcinoma. The rs385076 and rs775882 were associated with all three pathological types (p < 0.01).Conclusion: Besides providing candidate markers for identification of high-risk populations and early prevention of the disease, our research also provided new insight into anti-tumor strategies targeting inflammasomes and pyroptosis.Keywords: lung cancer, single nucleotide polymorphisms, pyroptosis, inflammasome, case-control study